Que saudades da professorinha... : histórias e memórias da educação de São José da Lagoa Tapada-PB (1968-1980) - Sousa, Rozilene Lopes de (2009)
The history of Brazilian education has given rise to researches who care to see the genesis of the educational system over time. From that perspective this paper analyzes the structure of the educational field in São José da Lagoa Tapada, the bias of primary education, from the creation of the School Genésio Araújo. It is argued, therefore, the importance of memories of teachers who worked primarily in accruals between the 1968 and 80s, in that city, in the form of narratives written to the (re) construction of significant moments in history Brazilian education and the city in focus. It is understood, therefore, that the study contributes to that from listening and writing oral histories of these issues teachers, discuss the teacher's identity and conceptions of education and society conveyed in the daily practices reported by the collaborators interviewed with order to see the reflections of Brazilian education, especially primary education, in the process of democratization of society.